Control design and voltage stability analysis of a droop-controlled electrical power system for more electric aircraft - Gao, Fei; Bozhko, Serhiy; Costabeber, Alessando; Asher, Greg; Wheeler, Patrick (Institute of Electrical and Electronics Engineers, 2017)
This paper focuses on the analysis of a single DC bus multi-generator Electrical Power System (EPS) for future More Electric Aircrafts (MEA). Within such a single bus paradigm, the paper proposes a detailed control design procedure and provides a stability analysis based on the derivation of the output impedance of the source subsystem and input impedance of the load subsystem, including control dynamics. The single bus characteristic is analyzed and the stability properties of the EPS are investigated when supplying constant power loads. In addition, the paper highlights the impact on stability of the number of parallel sources and of the power sharing ratio. The theoretical analysis is instrumental in designing an optimally stable single DC bus EPS. The key findings are validated by experimental results.